Correlation of Learning Outcomes in Islamic Religious Education Subjects with Religious Behavior of Junior High School Students - Murtadho, Fajar Ali; Sukir, Sukir (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2025)
Purpose of the study: The purpose of this study is to determine the learning outcomes of students in Islamic Religious Education, identify students' religious behavior, and analyze the relationship or correlation between the learning outcomes of Islamic Religious Education and students' religious behavior. Methodology: In this study, the researcher used a quantitative correlational approach. The data analysis technique used a statistical formula, namely product-moment correlation. Main Findings: From the data analysis, it was found that student learning outcomes in Islamic Religious Education were in the sufficient category with 38 respondents (74%), while students' religious behavior was also in the sufficient category with 41 respondents (80%). In addition, a positive correlation was found between Islamic Religious Education learning outcomes and students' religious behavior with a correlation coefficient of 0.336, which is included in the low relationship category.. Novelty/Originality of this study: This study provides new insights by empirically examining the correlation between learning outcomes in Islamic Religious Education and students’ religious behavior, an area often discussed theoretically but rarely measured quantitatively. The findings highlight how academic performance aligns with spiritual development, offering practical guidance for educators to integrate moral and cognitive growth in junior high school curricula.